Effects of CPAP on cardiorespiratory outcomes in patients with obstructive sleep apnea and heart failure: a systematic review - Marcia da Silva Martins; Rafael Saldanha dos Santos; Francisco Xavier de Araujo (Universidade de São Paulo, 2023)
ABSTRACT Obstructive sleep apnea (OSA) is a public health problem with a great economic impact. It is estimated that the prevalence of patients with OSA ranges from 4% to 6% of men and 2% to 4% of women in the general population. Strong evidence suggests that both sleep disorders and heart failure (HF) are related. Continuous positive airway pressure (CPAP) is the gold standard non-pharmacological treatment for this population. However, there is still a gap in the literature and its effects in patients with OSA and HF are not entirely clear. This study aimed to evaluate, by randomized clinical trials, the effects of positive pressure on cardiorespiratory function in patients with OSA and HF. Randomized clinical trials were included, with publication in the MEDLINE, PEDro, Cochrane Library, SciELO and PubMed databases and the risk bias was assessed using the PEDro scale. Six articles were included in this study, involving 165 participants. Our findings demonstrate that CPAP in the treatment of OSA in patients with HF promotes an increase in left ventricular ejection fraction, oxygen saturation and a reduction in blood pressure, apnea/hypopnea indices and awakenings from sleep during the night. We conclude that treatment with CPAP promotes an improvement in cardiorespiratory outcomes in patients with OSA and HF, improving the prognosis and reducing the risk of sudden death. However, their data must be cautiously interpreted considering the bias of the studies and their limitations.